Di Degradasi Habitat dan Studi Kondisi Makrozoobentos di Kawasan Ekosistem Mangrove yang Homogen - Lismarita Lismarita; M Ali Sarong; Ismul Huda; Samingan Samingan; Muhibbuddin Muhibbuddin; Yuri Gagarin (Jurnal Penelitian Pendidikan IPA, 2022)
Habitat degradation that occurs in the mangrove ecosystem will have an impact on the presence of associated biota found in the ecosystem, including macrozoobenthos. If it continues, it will threaten the sustainability of macrozoobenthos resources which are characterized by decreasing abundance and it is not even impossible that one day they will become extinct. The purpose of this research is to analyze the species composition of macrozoobenthos and to analyze the composition of mangrove species. This research was conducted in the mangrove ecosystem of Naga Permai Beach, Gampong Lhok and Gampong Pulo, Kuala Pesisir District, Nagan Raya Regency, Aceh Province in December 2021. The research method was quadrat sampling. The results showed that the macrozoobenthos species found consisted of 2 phylum, 3 classes, 7 families with 16 species